Development of an Impact Energy Absorption Structure by an Arc Shape Stroke Origami Type Hydraulic Damper - Jingchao Guan; Yuan Yao; Wei Zhao; Ichiro Hagiwara; Xilu Zhao (Shock and Vibration)
Cylindrical hydraulic dampers used to reduce impacts and vibrations typically have linear strokes. In this study, a new arc-shaped stroke-type origami hydraulic damper with a nonlinear damping performance was proposed. By examining the damping effect of the origami hydraulic damper, the damping force was found to be proportional to the square of the motion velocity. A nonlinear dynamics governing equation was established using the derived formula for the damping force of the origami hydraulic damper, and a numerical analysis using the Runge–Kutta method was established. An impact test device with an arc-shaped stroke was developed, and the error between the numerical analysis value of the impact displacement and the measured experimental value was confirmed to be sufficiently small. An impact verification experiment confirmed that the damping effect of the origami hydraulic damper increases with the input energy of the impact. By varying the diameter of the orifice hole, which is an important design factor for an origami hydraulic damper, the damping effect of the origami hydraulic damper was found to increase as the diameter of the orifice hole decreased. To examine the effect of the type of hydraulic oil inside the origami hydraulic damper, water and edible oil were used to conduct impact verification experiments, and it was found that the effect on the impact damping effect was relatively small.